2013
DOI: 10.1681/asn.2012090902
|View full text |Cite
|
Sign up to set email alerts
|

Brg1 Determines Urothelial Cell Fate during Ureter Development

Abstract: Developing and adult ureters express the epigenetic regulator Brg1, but the role of Brg1 in ureter development is not well understood. We conditionally ablated Brg1 in the developing ureter using Hoxb7-Cre and found that Brg1 expression is upstream of p63, Pparg, and sonic hedgehog (Shh) expression in the ureteral epithelium. In addition, epithelial stratification in the basal cells required Brg1-dependent p63 expression, whereas terminal differentiation of the umbrella cells required Brg1-dependent Pparg expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Also, mutations in certain genes induce hydronephrosis in animals and humans (41-43). It is interesting that orally administered SCFAs can also induce UPJ obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Also, mutations in certain genes induce hydronephrosis in animals and humans (41-43). It is interesting that orally administered SCFAs can also induce UPJ obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Around birth, the three epithelial and mesenchymal cell layers can be histologically clearly distinguished. 3,4 Embryologic experiments have shown that the survival, patterning, and subsequent differentiation of the primitive ureteric epithelium and its surrounding mesenchyme depend on each other. Genetic analysis has identified some of the trans-acting signals and the downstream transcription factors that regulate these cellular programs.…”
mentioning
confidence: 99%
“…Brg1-null mice die during the peri-implantation stage, whereas Brm-null mice develop normally (Bultman et al, 2000;Reyes et al, 1998). Recent studies showed that Brg1 is essential for development or homeostasis of various organs and cell types, including heart (Hang et al, 2010;Takeuchi et al, 2011), vasculature (Davis et al, 2013;Griffin et al, 2008Griffin et al, , 2011, ureter (Weiss et al, 2013), smooth muscle (Zhang et al, 2011) and neurons (Li et al, 2013;Matsumoto et al, 2006;Seo et al, 2005). In the intestine, Brg1 is essential for maintenance of intestinal stem cells (Holik et al, 2013).…”
Section: Introductionmentioning
confidence: 99%